Explication of Extrinsic Forearm Muscles On the Classification of Thumb Position Using High-Density Surface Electromyogram - Suhaimi, M. M.; Ghazali, A.S.; Jazlan, A.; Sidek, S.N. (International Journal of Integrated Engineering, 2023)
Muscles for hand functions and movements play a major role in basic daily activities such as writing and lifting objects. The main digit of the finger in differentiating the hand gesture is the thumb and its main muscles are intrinsic muscles. However, for transradial amputees, despite the loss of access to the intrinsic muscles, any information from the extrinsic muscles would be paramount and non-negotiable in creating a perfect hand prosthesis. As such, the research is dedicated to studying the relationship between extrinsic muscles located at the human’s forearm to characterize the actual thumb attitudes. A 64-channel HD-sEMG recording device together with a thumb force measuring platform was utilized to collect the required signals from 17 participants at several thumb angle positions namely zero-degrees, thirty-degree, sixty-degrees, and ninety-degree. For each position, the participants were required to place their thumbs on top of a load cell at relaxing (no force at all) and contact (30% of their individual Maximum Voluntary Contraction or known as MVC) conditions repetitively by following a designated trajectory. Feature extraction was performed by calculating the Root Mean Square (RMS) values of the HD-sEMG data collected from each channel. Six different classifiers have been used to classify the relationship between the forearm HD-sEMG and the corresponding thumb positions. As a result, LazyIBK obtained the highest correctly classified instances with 81.05%. The finding is significant in developing a dedicated control framework for a prosthetic hand for tansradial amputees that can operate as closely as normal.